An Investigation into the Concept of Liberation in Different Philosophical and Religious Traditions - Ottuh, Peter O. O.; Idjakpo, Onos Godwin (PREDESTINASI, 2020)
The concept of liberation is one of the most fundamental concepts, a central notion of many different religious and philosophical traditions in the world. People always have desires for safety, happiness, perfection and a particularly earnest desire for liberation from the bondage, suffering of body and mind. Every successive religion has been more or less influenced by the previous religions in theories as well as in practices, yet there exist some differences among them. Most of the prophetic religions believe that the path leading to liberation is the service of God or submission to His orders. On the other hand, some religions subscribe to rites and pillars. However, humans are living in the modern world, which is an amalgam of multiple cultures and religions. The potential threats of violence, wars and social evils, especially religious conflicts are always present. The comprehensive knowledge of several cultures and religions may bridge the gaps among different faith groups. Every religion or tradition must be understood as one kind of flower among several kinds of flowers in a big garden. As such, every religion has its particular values that deserved to be respected and protected. And the common purpose of all religions is to serve human needs. Thus, the essence of this work is to reveal the concept of Liberation within some philosophical school of thought. This research employs the method of Historical, Analytical and Comparative method to arrive at its conclusions.